TRAINING ON DIVERSIFICATION OF FISHERY PRODUCTS FOR FISHING COMMUNITIES IN MUARA SIKABALUAN, MENTAWAI ISLANDS, TO IMPROVE ECONOMIC RESILIENCE - Atifah, Yusni; Putri, Irma Leilani Eka; Holinesti, Rahmi; Fadillaturahmah, Fadillaturahmah (Pelita Eksakta, 2024)
The community of Sikabaluan Village primarily earns a living as fishermen. The obstacles in selling fishermen's products are related to the geographical location of Sikabaluan village, which has limited transportation between the village and areas outside the island. The issues found in the village of Sikabaluan are 1) The accumulation of fish during the harvest season, causing fish prices to tend to be lower than usual, even resulting in unsold fish that spoil, and 2) A lack of knowledge among the community regarding fish preservation. This relates to how to preserve fish so that it does not spoil quickly and has a longer shelf life, as well as how to utilize and prepare natural materials as natural preservatives. 3) There is a lack of skills among the community to process fishery products into other types of food, so that unsold fish can be transformed into other food types with higher market value. Therefore, it is necessary to provide assistance to the community of Sikabaluan village to enhance their knowledge regarding fish preservation and how to process fish into other types of food with high economic value. The method used in this service involves counseling and training for the community. This activity will be held in August 2024 and will be attended by 20 participants from the fishing community of Muara Sikabaluan village. The results of this activity show that (1) there is an increase in public knowledge about food and nutrition as well as innovations in fish processing. (2) The community has acquired skills in processing fish products into nuggets. (3) This knowledge and skill can serve as a foundation for businesses to meet the community's livelihood needs, thereby enhancing the economic situation of the community